2015
DOI: 10.1111/jsbm.12156
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Orientation and Service Innovation on Consumer Response: A B&B Case

Abstract: Extant studies have documented the effect of entrepreneurial orientation (EO) and innovation performance on firm-level outcomes. However, the underlying mechanisms of the specific aspects of EO (i.e., autonomy, risk-taking, and proactiveness)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 82 publications
2
21
0
Order By: Relevance
“…To define the relationship of how EO could affect CS, several authors have considered that new product development must go beyond to incorporate an innovative perspective with scarce resources, which allow the knowledge of how to deal with the market by taking risks and being competitive (Martin & Javalgi, 2016). Although prior research has established a previous step to get CS, considering service performance a direct relationship between EO and CS (Neck, Houghton, Sardeshmukh, Goldsby, & Godwin, 2013;Wang & Juan, 2016), it means that EO has been related in an indirect way with CS. Hence, this study aims to mainly define the direct effect for being oriented to entrepreneurship, which enables the remarking of the differentiation of the competitors by the consumers especially when the firm is sufficiently creative to offer new products, which depend on customer needs (Kollmann & Stöckmann, 2014).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…To define the relationship of how EO could affect CS, several authors have considered that new product development must go beyond to incorporate an innovative perspective with scarce resources, which allow the knowledge of how to deal with the market by taking risks and being competitive (Martin & Javalgi, 2016). Although prior research has established a previous step to get CS, considering service performance a direct relationship between EO and CS (Neck, Houghton, Sardeshmukh, Goldsby, & Godwin, 2013;Wang & Juan, 2016), it means that EO has been related in an indirect way with CS. Hence, this study aims to mainly define the direct effect for being oriented to entrepreneurship, which enables the remarking of the differentiation of the competitors by the consumers especially when the firm is sufficiently creative to offer new products, which depend on customer needs (Kollmann & Stöckmann, 2014).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…In this tone, we must identify innovation, risk-taking, and proactivity as an evolutionary routine, which permits the necessary-driven value-creation from taking advantage of opportunities that the market offers to become a chance in something reachable (Acar, Zehir, Özgenel, & Özşahin, 2013). In a global demand, where the particularities of selling are necessary to have a defined strategy based on the needs of customers, thus, an entrepreneur must be able to recognize characteristics of the market-i.e., physical, emotional, and psychological characteristics-which are to be expanded (Wang & Juan, 2016). The skills to determine the needs of the market arise when an entrepreneur knows how to point out customer orientation; if he or she is informed about changing customer needs in turn to pursue new opportunities of business, he or she will reach CS, applying limited resources that could be focused on leading company performance (Tajeddini, Elg, & Trueman, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The nine studies of family firms as contexts of analysis at the macro level confirmed that firms’ family nature is a prototypical feature that relates to consumer perceptions of authenticity in specific markets, such as wine and business-to-business industries (Massa, Helms, Voronov, & Wang, 2017; Tsui-Auch, 2005) or even a prototypical feature of innovation in industries such as tourism (Wang & Juan, 2016). The same prototypical feature was found to be relevant for a family-based brand (Santos, Burghausen, & Balmer, 2016), where the corporate family-based brand heritage fostered a sense of authenticity for the product brands of the same company.…”
Section: Resultsmentioning
confidence: 87%
“…The existing entrepreneurship approach literatures have recognized the significant of risk-taking by examine its impact at various business-level outcome (Bromiley, 1991). Studies revealed that taking risk is positively relates to a firm's new product performance (Wang & Juan, 2016;Aloulou, 2019) still others show negative influence such as Lechner and Gudmundsson (2014); Shan et al (2016).…”
Section: Individual Entrepreneurial Orientation (Ieo): Risk-taking Orientation Behaviours and Delinquent Behavioral Changementioning
confidence: 99%